MANIPULATION AS A WAY OF TRANSFORMATION OF SOCIAL CONSCIOUSNESS - Пода, Т. А. (Proceedings of the Kyiv Aviation Institute. Series: Philosophy. Cultural, 2016)
The article is devoted to the socio-philosophical analysis of the phenomenon of manipulation, identify of its components and factors that generate it.